2021
DOI: 10.1186/s12887-021-02687-z
|View full text |Cite
|
Sign up to set email alerts
|

The association between ambient air pollution and birth defects in five major ethnic groups in Liuzhou, China

Abstract: Background Studies suggest that exposure to ambient air pollution during pregnancy may be associated with increased risks of birth defects (BDs), but conclusions have been inconsistent. This study describes the ethnic distribution of major BDs and examines the relationship between air pollution and BDs among different ethnic groups in Liuzhou city, China. Methods Surveillance data of infants born in 114 registered hospitals in Liuzhou in 2019 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
1
6
1
Order By: Relevance
“…In the single pollutant analysis of NO 2 , we observed increases of 35–61% in the risk of CL/P, as well as increases of 60–66% in the risk of CPO per IQR increase in NO 2 in all months of the first trimester of pregnancy. Our estimates supported the results from the studies performed by Zhu et al in the U.S. [ 11 ] and Wang et al in China [ 18 ], which reported an aOR of 3.64 (95% CI 1.73, 7.66) for CPO per IQR increase during weeks 3–8 of pregnancy and a RR of 1.19 (95% CI 1.03, 1.36) for cleft palate per 10 μg/m 3 increase during the first trimester of pregnancy, respectively. No other previous studies that estimated the effect of NO 2 found significant results [ 18 , 26 , 28 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the single pollutant analysis of NO 2 , we observed increases of 35–61% in the risk of CL/P, as well as increases of 60–66% in the risk of CPO per IQR increase in NO 2 in all months of the first trimester of pregnancy. Our estimates supported the results from the studies performed by Zhu et al in the U.S. [ 11 ] and Wang et al in China [ 18 ], which reported an aOR of 3.64 (95% CI 1.73, 7.66) for CPO per IQR increase during weeks 3–8 of pregnancy and a RR of 1.19 (95% CI 1.03, 1.36) for cleft palate per 10 μg/m 3 increase during the first trimester of pregnancy, respectively. No other previous studies that estimated the effect of NO 2 found significant results [ 18 , 26 , 28 ].…”
Section: Discussionsupporting
confidence: 92%
“…For instance, a case–control study including 653 cases from Taiwan, China reported the risk of CL/P was increased in relation to O 3 levels in the first (aOR = 1.20, 95% CI 1.02, 1.39) and the second month of pregnancy (aOR = 1.25, 95% CI 1.03, 1.52) [ 6 ], Another cohort study performed by Zhao et alin Wuhan, China announced significant associations for CPO in the second and the third month of pregnancy, with aORs of 1.21 (95% CI 1.03, 1.42) and 1.18 (95% CI 1.02, 1.37), respectively [ 15 ]. Unfortunately, we failed to detect a positive effect of O 3 on CL/P or CPO in Changsha, China in this study, as did most of the previous studies [ 10 , 12 , 18 ].…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…In this hospital-based study, we used Guilin City's perinatal BD monitoring data to describe the epidemiological characteristics of common BDs and review the etiological identification of these BDs in Guilin, Guangxi province, China. The total prevalence of BDs was 13.55 per 1,000 births from 2018 to 2020, which was lower than the prevalence rate of 19.53 per 1,000 births in Liuzhou, another city in Guangxi ( 20 ).…”
Section: Discussionmentioning
confidence: 64%
“…Finally, although several relevant covariates were controlled for in this study, we cannot eliminate the possibility of residual confounding from other factors, such as e genetic problems of parents and fetal, maternal complications, passive smoking, and time spent outdoors. Maternal smoking and alcohol use were not controlled for because < 0.3% of the mothers during pregnancy reported smoking or drinking alcohol ( 22 ).…”
Section: Discussionmentioning
confidence: 99%